Catalan Independence and the Crisis of Sovereignty
XV, 260 p. 4 illus., 3 illus. in color.
Keywords: This book explores the conflict between the Catalan project to become independent and the Spanish state’s opposition to any attempt of secessionism. The volume addresses some of the key political and academic issues of contemporary European societies: nationalism, separatism and sovereignty. The banned referendum in Catalonia in October 2017 unveiled the existence of multiple crises, from territorial to economic and political. Indeed, the Catalan issue is about the crisis of sovereignty: who holds legitimacy to make decisions, and who is in power legally and politically? The book is structured according to three themes: sovereignty and its people, where the realignment to independence, populism and the definition of the demos are discussed; collective identities and actions, to account for the shaping of ‘us’, the importance of collective memory and the cross-alliances forged during the referendum; and internationalization, focusing on Europeanisation, international media and comparative constitutional perspectives. Óscar García Agustín is Associate Professor in the Department of Culture and Learning at Aalborg University, Denmark. He is Head of the DEMOS research group. He is the author of Left-Wing Populism (2020), Solidarity and the ‘Refugee Crisis’ in Europe (with Martin Bak Jorgensen, 2018), and Podemos and the New Political Cycle (with Marco Briziarelli, 2018).